Membangun Perilaku Anti Acquired Immune Deficiency Syndrome (AIDS)- Human Immunodeficiency Virus (HIV) Pada Kelompok Remaja - Mardalena, Mardalena; Apriani, Selvy (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
Adolescent is the category of relatively young group with energetic, responsive, and highly curious characteristics. Effective adolescent guidance can guarantee better future of national generation. â€œWhere there is a healthy body, there is a healthy mindâ€ is the proverb that suits adolescent best, including those in Banyuasin. However, healthy physical and mind development should be in line with the control of high curiosity in several aspects. Uncontrolled curiosity may lead to inappropriate life choices among adolescent. Adolescent tends to be curious about new things, especially those related to pseudo satisfactions. Such behavior may lead adolescent to one infectious disease called Acquired Immune Deficiency Syndrome (AIDS). This disease is caused by a virus called Human Immunodeficiency Virus (HIV). This disease may drastically decrease humanâ€™s immune system, which eventually leads to death. This is the condition that adolescent must avoid and stay away from. Therefore, the development of understanding and awareness against AIDS through socialization and education among adolescent is necessary since there are potential risks that threaten the future of national generation. Anti-AIDS adolescent development program has been implemented through socialization and education on High School students. Implemented development has improved the adolescentâ€™s understanding and awareness, especially among High School students in Banyuasin. This development program has become the pioneer of the anti-AIDS-HIV adolescent behavior development.